Kebijakan Pengembangan Profesionalisme Berkelanjutan Guru PNS - Riyadin, Slamet (Universitas Muhammadiyah Sidoarjo, 2016)
Teacher was one of humankind as an engine in the educational process. In the process of education in schools, teachers were holding double duty as a teacher and educator. As a teacher in charge of giving some learning materials professionally, while as an educator in charge of giving guide and nurture their students to become skilled human, active, creative and independent. Therefore, policy of development for the teacher was needed. It aimed to develop and enhance the competence and capacity of teachers in accordance with their expertise. It was done through education and training in the form of in-house training, internship program, partnership schools, distance learning, specialized training, short courses, internal coaching by the school, as well as continuing education. In addition, there were education discussion, seminars, workshops, research, writing books / materials, manufacture instructional media, and making technology/artwork. Policy of development professionalism teacher accordance in Government Regulation Number 74 of 2008 on Teachers, Regulation of the Minister of Administrative Reform and Bureaucratic Reform Number 16 of 2009 on Functional Position Teacher and credit figures. However, there are weaknesses in this policies that sanction teachers who did not implemented explicitly and in writing.